2009
DOI: 10.1080/19361520903120228
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Emotional Abuse and Relational Functioning: Social Support and Internalizing Symptoms as Moderators

Abstract: Emotional abuse in childhood has deleterious consequences across development and may be a key factor that underlies all forms of childhood maltreatment. This study examined the association between emotional abuse and relationship functioning among 139 low-income, African American 8-to 12-year-old children, with internalizing symptoms and social support from family, peers, and teachers tested as moderators. Emotional abuse was significantly negatively correlated with both peer and family relationship functionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…This study was part of a larger investigation of female mother-child dyads recruited for the project(Gabalda, Broth, Thompson, & Kaslow, 2009; Gabalda, Thompson, & Kaslow, 2010; Kaslow & Thompson, 2008; Mitchell et al, 2006; Owen, Thompson, & Kaslow, 2006; Owen et al, 2008; Owen, Thompson, Shaffer, Jackson, & Kaslow, 2009). Trained and supervised weekly by the principal investigator, team members (undergraduates, graduate students, and postdoctoral fellows) ( n = 32, 25 of whom were female and 17 of whom self-identified as African American) recruited participants from: (1) medical and emergency care clinics in the general hospital and associated children's hospital and (2) local women's shelters.…”
Section: Methodsmentioning
confidence: 99%
“…This study was part of a larger investigation of female mother-child dyads recruited for the project(Gabalda, Broth, Thompson, & Kaslow, 2009; Gabalda, Thompson, & Kaslow, 2010; Kaslow & Thompson, 2008; Mitchell et al, 2006; Owen, Thompson, & Kaslow, 2006; Owen et al, 2008; Owen, Thompson, Shaffer, Jackson, & Kaslow, 2009). Trained and supervised weekly by the principal investigator, team members (undergraduates, graduate students, and postdoctoral fellows) ( n = 32, 25 of whom were female and 17 of whom self-identified as African American) recruited participants from: (1) medical and emergency care clinics in the general hospital and associated children's hospital and (2) local women's shelters.…”
Section: Methodsmentioning
confidence: 99%
“…Research has clearly demonstrated the link between violent family contexts, including inter-parental violence and maltreatment, and reduced perceptions of family social support (Gabalda, Broth, Thompson, & Kaslow, 2009;Merrill, Thomsen, Sinclair, Gold, & Milner, 2001;Pepin & Banyard, 2006). Similarly, we know that victimization at the hands of peers is associated with reduced levels of peer social support (Demaray & Malecki, 2003;Flaspohler, Elfstrom, Vanderzee, Sink, & Birchmeier, 2009;Holt & Espelage, 2007;Pepin & Banyard, 2006;Rigby, 2000).…”
Section: Poly-victimization and Social Supportmentioning
confidence: 99%
“…Research showed that the positive moral personality of college students were significantly negatively correlated with anti-social behaviors (e.g., violation, addiction, and attack tendencies; Zhang, 2012). In the developmental period of moral personality, as a childhood experience, childhood psychological abuse was closely related to individual personality characteristics (Gabalda et al, 2009;Martinotti et al, 2009;Conger et al, 2010;Auslander et al, 2016). Studies have shown that psychological abuse was negatively related to extroversion, and individuals who experienced more psychological abuse showed high levels of neuroticism, impulsion, and other negative personality tendencies (Li et al, 2017).…”
Section: Moral Personality As a Mediatormentioning
confidence: 99%